TCTN3 Mutations Cause Mohr-Majewski Syndrome - Thomas, Sophie; Legendre, Marine; Saunier, Sophie; Bessières, Bettina; Alby, Caroline; Bonnière, Maryse; Toutain, Annick; Loeuillet, Laurence; Szymanska, Katarzyna; Jossic, Frédérique; Gaillard, Dominique; Yacoubi, Mohamed Tahar; et al. (American journal of human genetics, 2012)
Orofaciodigital syndromes (OFDSs) consist of a group of heterogeneous disorders characterized by abnormalities in the oral cavity, face, and digits and associated phenotypic abnormalities that lead to the delineation of 13 OFDS subtypes. Here, by a combined approach of homozygozity mapping and exome ciliary sequencing, we identified truncating TCTN3 mutations as the cause of an extreme form of OFD associated with bone dysplasia, tibial defect, cystic kidneys, and brain anomalies (OFD IV, Mohr-Majewski syndrome). Analysis of 184 individuals with various ciliopathies (OFD, Meckel, Joubert, and short rib polydactyly syndromes) led us to identify four additional truncating TCTN3 mutations in unrelated fetal cases with overlapping Meckel and OFD IV syndromes and one homozygous missense mutation in a family with Joubert syndrome. By exploring roles of TCTN3 in human ciliary related functions, we found that TCTN3 is necessary for transduction of the sonic hedgehog (SHH) signaling pathway, as revealed by abnormal processing of GLI3 in patient cells. These results are consistent with the suggested role of its murine ortholog, which forms a complex at the ciliary transition zone with TCTN1 and TCTN2, both of which are also implicated in the transduction of SHH signaling. Overall, our data show the involvement of the transition zone protein TCTN3 in the regulation of the key SHH signaling pathway and that its disruption causes a severe form of ciliopathy, combining features of Meckel and OFD IV syndromes.